Test Reliability as A Foundation for Accurate and Objective Assessment in Islamic Education - Mariana; Dina Hermina (JIS: Journal Islamic Studies, 2026)
This study examines the role of test reliability, particularly the test–retest method, in strengthening the quality of assessment within Islamic Education. The study is motivated by the growing need for accurate, consistent, and accountable assessment instruments to support meaningful learning evaluation. While previous studies have extensively discussed validity and authentic assessment, limited attention has been given to the contribution of test reliability as a foundation for objective assessment practices in Islamic Education. This research employed a qualitative approach using library research methods. Data were collected from books, scientific journal articles, and relevant academic publications published within the last ten years and analyzed through content analysis techniques. The findings reveal that test reliability plays a crucial role in ensuring the consistency, stability, and trustworthiness of assessment results. Furthermore, the test–retest method provides an effective framework for evaluating score stability over time and minimizing measurement errors. In the context of Islamic Education, reliable assessment instruments support fair evaluation, strengthen data-based decision-making, and align with Islamic values emphasizing accuracy, honesty, and accountability. The study concludes that test reliability serves as an essential component in developing high-quality assessment systems capable of supporting effective learning evaluation and improving educational outcomes in Islamic Education.